The perception of Physical Education teachers about culturally oriented curriculum writing (Research, Society and Development, 2021)
Physical Education’s cultural curriculum questions the hegemony of physical manifestations and the significance of the privileged groups. Based on the perspective of difference as society’s wealth and on the construction of a teaching profession that is attentive towards diversity, it joins forces with the school’s Pedagogical Project, strengthening the community’s cultural heritage as a base for choosing teaching themes. With this in mind, the present study seeks to analyze the perception of Physical Education teachers regarding the current pedagogical guidelines for the subject that are contained in the Institutional Political Pedagogical Project (2017-2020) for Colégio Pedro II, which is written in a culturally oriented manner. As a methodological tool, we used a questionnaire with open and closed questions to interview 33 teachers and then applied content analysis based on Bardin (2011). While analyzing the answers, four categories emerged:  Citizen education; Valuing diversity and difference; Valuing minority cultures / problematizing relationships of power; Student interest and valuing one’s own culture. We concluded that the cultural curriculum strongly influences the guidelines for the pedagogical actions conducted by the group of teachers in question and that there is an understanding among the group, momentary though it may be, regarding what the cultural curriculum seems to be. The curricular modifications that have been observed seem to demonstrate an abandonment of the developmental perspective in this institution.